A Didactical Design of Teaching Decimal Numbers for Fourth-Grade Elementary Students - Mitria Mitria; Nyiayu Fahriza Fuadiah; Yunika Lestaria Ningsih (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
Learning obstacles to decimal concepts at the elementary level can hinder students' mathematical development in subsequent grades. A common difficulty lies in interpreting decimal values, which requires a well-structured instructional design to minimize these barriers. This study aims to develop a didactic design for teaching decimals based on an analysis of learning barriers and learning trajectories. Using Didactical Design Research (DDR), this study was conducted through three stages: prospective analysis, metapedadidactic analysis, and retrospective analysis. Data were collected through interviews, tests, documentation, and video recordings. Initially, learning barriers in ontogenic, epistemological, and didactic aspects were identified in fifth-grade students who had already learned decimals. Based on these findings, a Hypothetical Learning Trajectory was developed and implemented with 19 fourth-grade students who had not yet learned decimals. The results showed that the didactic design significantly improved students' ability to interpret decimals and strengthened their understanding of decimal operations. These findings underscore the importance of addressing learning obstacles in instructional design and recommend the integration of the DDR approach in mathematics teaching to enhance conceptual understanding from an early stage.